2009
DOI: 10.1038/aja.2009.26
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of seminal plasma from asthenozoospermia patients reveals proteins that affect oxidative stress responses and semen quality

Abstract: Asthenozoospermia (AS) is a common cause of human male infertility. In one study, more than 80% of the samples from infertile men had reduced sperm motility. Seminal plasma is a mixture of secretions from the testis, epididymis and several male accessory glands, including the prostate, seminal vesicles and Cowper's gland. Studies have shown that seminal plasma contains proteins that are important for sperm motility. To further explore the pathophysiological character of AS, we separated the seminal plasma prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 38 publications
4
105
1
Order By: Relevance
“…Clinical studies showed that oral antioxidant treatment appeared to improve sperm DNA integrity and outcomes of in vitro fertilization with intracytoplasmic sperm injection among patients with sperm DNA damage or other male infertility [9,10]. In asthenozoospermia patients, the high level of ROS in semen may be associated with the downregulation of a DJ-1 protein, which is involved in the control of oxidative stress [11].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies showed that oral antioxidant treatment appeared to improve sperm DNA integrity and outcomes of in vitro fertilization with intracytoplasmic sperm injection among patients with sperm DNA damage or other male infertility [9,10]. In asthenozoospermia patients, the high level of ROS in semen may be associated with the downregulation of a DJ-1 protein, which is involved in the control of oxidative stress [11].…”
Section: Introductionmentioning
confidence: 99%
“…[1]. Introducing proteomic analysis of human seminal fluid has led to more detailed analysis and has indicated a large number of extracellular proteins, proteases and other proteins secreted by testes, prostate and other male accessory glands [2][3][4][5]. However, the structure-function relationship of seminal plasma proteins at the molecular level and the relation of more basic questions to particular clinical end points is still insufficiently explored.…”
Section: Introductionmentioning
confidence: 99%
“…Yamakawa et al (2007) identified up to 501 polypeptide spots in SP from fertile men by a proteomic approach based on 2D-differential gel electrophoresis (2D-DIGE), and used this normalized standard map of SP proteins to characterize the differences in the proteic expression between fertile and azoospermic patients. Wang et al (2009), on the other hand, identified 625 proteins in SP from fertile men by LC-MS/MS analysis. They identified 45 up-regulated proteins and 56 down-regulated proteins in a group of asthenozoospermic patients compared with the control subjects.…”
Section: Proteomic Identification Of Fertility and Infertility Markersmentioning
confidence: 99%
“…Moreover, the quantities of two epididymal secretory proteins, protein E1 and epididymal secretory protein E4, were increased in asthenozoospermic SP. This study identified a rich source of biomarker candidates for male infertility, and suggested that functional abnormalities of the epididymis, prostate, and seminal vesicles can impact sperm quality (Wang et al, 2009). …”
Section: Proteomic Identification Of Fertility and Infertility Markersmentioning
confidence: 99%
See 1 more Smart Citation